PENGARUH SUBSTITUSI TEPUNG TEMPE DAN PENAMBAHAN TEPUNG BROKOLI TERHADAP DAYA TERIMA CRACKERS SEBAGAI MAKANAN SELINGAN WANITA USIA SUBUR (WUS) PENCEGAH ANEMIA - Nandhite Madhah Ningtyas; Asrul Bahar (Jurusan Gizi Poltekkes Kemenkes Bandung, 2025)
Crackers substituted tempeh flour and added broccoli flour can used as good alternative in prevent anemia, especially for Women of Childbearing Age (WCA). The purpose of this study was to determine the effect of substitution of tempeh flour, addition of broccoli flour, and the interaction of tempeh flour and broccoli flour on the acceptability of crackers, and to find out the best product in terms of nutritional content (carbohydrates, protein and iron). Type of research is Experimental with Completely Randomized Design (CRD) 2 factors; tempeh flour factor 3 levels (10%, 20% and 30%) and broccoli flour factor 2 levels (15% and 20%) in 6 modified formulas. The results of hedonic test on 60 untrained panelists were analyzed using two-way ANOVA test and subsequent tests using Duncan's test. T3B1 with 30% tempeh flour substitution and 15% broccoli flour addition was chosen as the best formula with nutritional content per 100grams; carbohydrates 59.80%, protein 22.04% and iron 5.73mg. The best crackers formula in a 7gram serving size is recommended for WCA consume 4-5 pieces a day to prevent anemia.